Islamic Branding Strategy Through Audience's Reception - Santoso, Rahmania; Prasetyo, Bambang Dwi (Technium Social Sciences Journal, 2021)
Islamic Branding is an approach to branding with Sharia Principles. Over time, Islamic Branding has become one of the strategies used in product marketing. The aims of this research to analyze the related topic towards audience reception and identifying the position of meaning for the Islamic Branding Strategy in Advertising Sahaja Products. This research used a qualitative research approach with the reception analysis method. The method highlights Stuart Hall's two concepts of encoding and decoding. The subjects of this research were seven members of the Islamic organization Nasyiatul 'Aisyiyah. The data were analyzed using two orders of signification by Roland Barthes (encoding) and in-depth interviews (decoding). The results of this research indicated the reception caused by the audiences, in understanding the meaning of the message can vary depending on the intensity of product use. The experience that has been felt and knowledge possessed. Thus, not all audiences can receive the message in full.